2022
DOI: 10.31989/ffhd.v12i3.900
|View full text |Cite
|
Sign up to set email alerts
|

Anti-allergic activity of an ethanol extract of bunching onion (Allium fistulosum), a traditional vegetable from Osaka

Abstract: Introduction: The incidences of allergic diseases such as allergic rhinitis, atopic dermatitis, asthma, and food allergies are rising in developed countries. Mast cells play critical roles in various biologic processes related to allergic diseases, including expressing the high-affinity receptor for immunoglobulin (Ig) E on their surface. The interaction of multivalent antigens with surface-bound IgE causes the secretion of granule-stored mediators, as well as the de novo synthesis of cytokines. These mediator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…for attenuating allergenic activity of roasted cod, which also agreed with a previous study demonstrating the anti-allergic activity of bunching onion ( Allium fistulosum ). 27 Moreover, the anti-allergenic effect appeared to significantly and inversely correlate with TAA and TPC. Q-TOF-MS/MS analysis in our recent study identified the principal phenolic constituents of the methanolic extract of Chinese chive.…”
Section: Resultsmentioning
confidence: 93%
“…for attenuating allergenic activity of roasted cod, which also agreed with a previous study demonstrating the anti-allergic activity of bunching onion ( Allium fistulosum ). 27 Moreover, the anti-allergenic effect appeared to significantly and inversely correlate with TAA and TPC. Q-TOF-MS/MS analysis in our recent study identified the principal phenolic constituents of the methanolic extract of Chinese chive.…”
Section: Resultsmentioning
confidence: 93%
“…The health benefits and human immune response, conditioned by the content of bioactive compounds and their valuable features [10], which, in turn, play an important role in enhancing food functionality, depend on several factors [11][12][13].The way the fruit is used and how it is processed (raw, cooked, frozen), is one of the factors to be considered in estimating functionally [14] of different crops including eggplants.…”
Section: Introductionmentioning
confidence: 99%